Fundamentals of thermal-fluid sciences - Cengel, Yunus A. (McGraw-Hill Higher Education, 2012)
The best-selling Fundamentals of Thermal-Fluid Sciences is designed for the non-mechanical engineering student who needs exposure to key concepts in the thermal sciences in order to pass the Fundamentals of Engineering (FE) Exam. The text is made up of Thermodynamics, Heat Transfer and Fluids. Like all the other Cengel texts, it uses a similar pedagogical approach, by using familiar everyday examples followed by theory and analysis. This edition features a return of Power and Refrigeration Cycles coverage in a revised and streamlined new chapter as well as more examples featuring sustainability and green technology. Additionally, the artwork is substantially revised and improved with more inclusion of three-dimensional figures.